Inland water transport development possibilities – case study of lower Vistula river - Tomasz Nowakowski (Archives of Transport, 2015)
Among different transportation modes, inland water transport is recognized as a low-cost, environmentally friendly way of transporting. The use of this mode in Poland encounters many challenges. Thus, the investigation of development possibilities by analysing the revitalization profitability and navigability restoration of Lower Vistula river should be explored. Following this, the article includes the summary of obtained results of the project INWAPO carrying out and regards development of infrastructure and sea/river ports, demand forecast for transportation, external costs estimation and the main benefits from lower Vistula river revitalization. The main analysis is done with the assumption of IV (or higher) navigable class of the Vistula river.